2001
DOI: 10.2525/jshita.13.97
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Harvesting End-Effector for Eggplants.

Abstract: A robotic harvesting system, which emulates the fruit recognition, approach, and picking This study showed the great feasibility of automating the basic harvesting motion for eggplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In addition, vegetables such as aubergines need to be carefully harvested, and only a cutting method is valid since any plucking technique could damage the plant [48]. Finally, this particular crop was also chosen because there are few research studies on it [30,49,50], and therefore, it offers new opportunities for future work.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, vegetables such as aubergines need to be carefully harvested, and only a cutting method is valid since any plucking technique could damage the plant [48]. Finally, this particular crop was also chosen because there are few research studies on it [30,49,50], and therefore, it offers new opportunities for future work.…”
Section: Introductionmentioning
confidence: 99%
“…Hayashi et al [65,66] developed a picking robot for the eggplant cultivated in V-frame, as shown in Figures 31 and 32. This type of robot consists of a five-DOF articulated robotic arm, a vision processing, and a mobile platform.…”
Section: A Picking Robot For V-frame Cultivationmentioning
confidence: 99%
“…Harvesting end-effector 5 The harvesting end-effector is an important tool to pick up the fruit after the manipulator end reaches the fruit. It was composed of a fruit-grasping mechanism, a size-judging mechanism, and a peduncle-cutting mechanism.…”
Section: System Componentsmentioning
confidence: 99%